2015 Beers criteria medication review in assisted living facilities. Issue 11 (November 2018) - Chun, Jessica C.; Appel, Susan J.; Simmons, Steven
ABSTRACT: Background and purpose: The elderly population is expected to double by 2050 with falls and hospitalizations due to adverse drug events having a major effect on health and quality of life. With the release of the revised 2015 American Geriatrics Society (AGS) Beers criteria, usage of potentially inappropriate medications (PIMs) should be studied to determine their effect on falls and hospitalizations in frail populations such as those in assisted living facilities. Methods: This quality improvement project used a retrospective chart review on residents from a purposive sample of two assisted living facilities in Northern Virginia. Residents were aged ≥65 and lived at the facility for at least 6 months and were not enrolled in hospice and/or palliative care or living in the dementia unit. The 2015 AGS Beers criteria were used to evaluate the effect of PIMs on falls and hospitalization rates. Conclusions: This project did not find statistical significance between PIMs and falls ( p = .276). A favorable, but not statistically significant trend, was noted between PIMs and hospitalizations ( p = .079). Implications for practice: Understanding the effect of PIMs on falls and hospitalizations could help providers improve prescribing practices for the elderly population who are at the greatest risk for potential adverse effects from polypharmacy.